Advances in Service and Industrial Robotics Proceedings of the 26th International Conference on Robotics in Alpe-Adria-Danube Region, RAAD 2017 - Ferraresi, Carlo; Quaglia, Giuseppe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume contains the proceedings of the 26th International Conference on Robotics in Alpe-Adria-Danube Region, RAAD 2017, held at the Polytechnic University of Turin, Italy, from June 21-23, 2017. The conference brought together academic and industrial researchers in robotics from 30 countries, the majority of them affiliated to the Alpe-Adria-Danube Region, and their worldwide partners. RAAD 2017 covered all major areas of R&D and innovation in robotics, including the latest research trends. The book provides an overview on the advances in service and industrial robotics. The topics are presented in a sequence starting from the classical robotic subjects, such as kinematics, dynamics, structures, control, and ending with the newest topics, like human-robot interaction and biomedical applications. Researchers involved in the robotic field will find this an extraordinary and up-to-date perspective on the state of the art in this area.
Scalera, Enrico Mazzon, Paolo Gallina, Alessandro Gasparetto -- Spring design for motor torque reduction in articulated mechanisms, by Paolo Boscariol, Giovanni Boschetti, Paolo Gallina, Chiara Passarini -- A robotic design for a MIM based technology, by Hermes Giberti, Luca Sbaglia -- Robust One-Shot Robot Programming by Demonstration using Entity-based Resources, by Eric Mathias Orendt, Michael Riedl, Dominik Henrich -- The "Robot Mechanics" course experience at Politecnico di Milano, by Hermes Giberti, Enrico Fiore -- Mechatronic Design and Prototype of a 4-DOFs Hot Wire CNC FoamCutting Machine, by Giorgio Figliolini, Rea Pierluigi, Carlo Cocomello -- Robotic grippers -- Development of a NEMS-Technology based Nano Gripper, by Andrea Veroli, Alessio Buzzin, Rocco Crescenzi, Fabrizio Frezza, Giampiero de Cesare, Vito D'Andrea, Francesco Mura, Matteo Verotti, Alden Dochshanov, Nicola Pio Belfiore -- A 3-Finger Robotic Gripper for Grasping Fabrics Based on Cams-Followers Mechanism, by Panagiotis Koustoumpardis, Sotiris Smyrnis, Nikos Aspragathos -- Experimental results for QuBu Gripper: a 3-Jaw electric gripper, by Luca Girolamo Butera, Giuseppe Quaglia -- Experimental evaluation and comparison of low-cost adaptive mechatronic grippers, by Giovanni Carabin, Ilaria Palomba, Dominik Matt, Renato Vidoni -- The experience at University of L'Aquila on shape memory alloys actuators, by Francesco Durante, Pierluigi Beomonte Zobel, Terenziano Raparelli -- Humanoids & cognitive systems.
Keywords: Control engineering; Robotics; Automation; Mechanical engineering; Biomedical engineering; Industrial engineering; Production engineering; Multibody systems; Vibration; Mechanics, Applied; Control, Robotics, Automation; Mechanical Engineering; Biomedical Engineering and Bioengineering; Industrial and Production Engineering; Multibody Systems and Mechanical Vibrations